Edison [videorecording (DVD)] - Ferrari, Michelle; Murphy, Michael, 1938-; Gitelman, Lisa; Myhrvold, Nathan (PBS, 2015)
Documentary about Thomas Edison that explores the complex alchemy that accounts for the enduring celebrity of America's most famous inventor. It offers new perspectives on the man and his milieu, and illuminates not only the true nature of invention, but its role in turn-of-the-century America's rush into the future.